2011
DOI: 10.2166/wst.2011.779
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between turbidity and total suspended solids concentration within a combined sewer system

Abstract: This article confirms the existence of a strong linear relationship between turbidity and total suspended solids (TSS) concentration. However, the slope of this relation varies between dry and wet weather conditions, as well as between sites. The effect of this variability on estimating the instantaneous wet weather TSS concentration is assessed on the basis of the size of the calibration dataset used to establish the turbidity - TSS relationship. Results obtained indicate limited variability both between site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(45 citation statements)
references
References 22 publications
(18 reference statements)
1
40
0
2
Order By: Relevance
“…The latter is probably the predominant source for this increase. Indeed, this deposits resuspension phenomenon during rainfall events has been demonstrated in various studies (CHEBBO et al, 2003;GROMAIRE et al, 2006;HANNOUCHE et al, 2011). The dry weather period particularly long (11 days) preceding this event is certainly the cause of the important increase in the fluxes due to a large stock of sediments rich in COD.…”
Section: Daily Fluxes Of Pollutantsmentioning
confidence: 60%
“…The latter is probably the predominant source for this increase. Indeed, this deposits resuspension phenomenon during rainfall events has been demonstrated in various studies (CHEBBO et al, 2003;GROMAIRE et al, 2006;HANNOUCHE et al, 2011). The dry weather period particularly long (11 days) preceding this event is certainly the cause of the important increase in the fluxes due to a large stock of sediments rich in COD.…”
Section: Daily Fluxes Of Pollutantsmentioning
confidence: 60%
“…Hannouche et al [41] confirmed the possible successes of using turbidity in assessing TSS within a combined sewer system; because the turbidity-TSS relationships show linearity regardless of weather conditions and most of them tend to pass close to the origin.…”
Section: Resultsmentioning
confidence: 92%
“…Discussing the uncertainties through this conversion would exceed the scope of this paper and are therefore not presented here. The reader is referred to the literature [11][12][13].…”
Section: Calculation Of Continuous Tss Time Seriesmentioning
confidence: 99%